KARAKTERISTIK DAN KESESUAIAN HABITAT RUSA TIMOR (Cervus timorensis) DI UNIVERSITAS RIAU - Mandala Yohannes Saputra; Defri Yoza; Evi Sribudiani (JURNAL ILMU-ILMU KEHUTANAN, 2021)
The breeding of Timor deer at the University of Riau was successful due to the high adaptability of the Timor deer outside their habitat. Maintaining the success of Timor deer breeding at the University of Riau the need for direct observation of the environment and the availability of food at the likely location of Timor deer breeding to avoid undesirable things. This research was conducted to be a reference for better management of Timor Deer's breeding efforts at the University of Riau. The materials and tools used are moisture meters, measuring instruments, cameras, compasses, tape measures, ropes, pH meters and clinometers. The method of investigation used is the census method using the path system. The study area of 2.07 ha with the census method records the water conditions, the topography, the protection of the canopy, the vegetation, the temperature and the humidity, which were not previously known. For an investigation area of 2.07 ha, a plot of 20 m width and 5000 m length is needed by drawing a line of intersection for population indications observed in the prospective breeding area. The results showed that the physical location of the potential stag breeding at Riau University could very well be determined and developed as a breeding ground for Timor stags. Suitability of Timor-Deer habitat (Cervus timorensis) at potential breeding grounds of the University of Riau supports various forest types, shade trees, feed types, roofing stratification and plant vegetation for the Timor-Deer breed (Cervus timorensis). The availability of biotics in breeding candidates is considered appropriate for the survival of the Timor-deer.